SIRT6 Is Involved in the Progression of Ovarian Carcinomas via β-Catenin-Mediated Epithelial to Mesenchymal Transition - Bae, Jun Sang; Noh, Sang Jae; Kim, Kyoung Min; Park, See-Hyoung; Hussein, Usama Khamis; Park, Ho Sung; Park, Byung-Hyun; Ha, Sang Hoon; Lee, Ho; Chung, Myoung Ja; Moon, Woo Sung; Cho, Dong Hyu; et al. (Frontiers in Oncology, 2018)
SIRT6 is involved in various cellular signaling pathways including those involved in tumorigenesis in association with β-catenin. However, the role of SIRT6 in tumorigenesis has been controversially reported and the studies on the role of SIRT6 in ovarian cancers is limited. In this study, we evaluated the expression and roles of SIRT6 in conjunction with the expression of active β-catenin in 104 human ovarian carcinomas and ovarian cancer cells. In human ovarian carcinomas, the expressions of SIRT6 and active β-catenin were associated with higher tumor stage, higher histologic grade, and platinum-resistance. Moreover, nuclear expression of SIRT6 (104 ovarian carcinomas; P = 0.010, 63 high-grade serous carcinomas; P = 0.040) and activated β-catenin (104 ovarian carcinomas; P = 0.013, 63 high-grade serous carcinomas; P = 0.005) were independent indicators of shorter overall survival of ovarian carcinoma patients in multivariate analysis. In OVCAR3 and OVCAR5 ovarian cancer cells, knock-down of SIRT6 significantly inhibited the migration and invasion of cells, but did not inhibit the proliferation of cells. SIRT6-mediated invasiveness of ovarian cancer cells was associated with the expression of epithelial-to-mesenchymal transition-related signaling molecules such as snail, vimentin, N-cadherin, E-cadherin, and activated β-catenin. Especially, SIRT6-mediated increase of invasiveness and activation of epithelial-to-mesenchymal transition signaling was attenuated by knock-down of β-catenin. In conclusion, this study suggests that SIRT6-β-catenin signaling is involved in the epithelial-to-mesenchymal transition of ovarian cancer cells, and the expression of SIRT6 and active β-catenin might be used as indicators of poor prognosis of ovarian carcinoma patients. In addition, our results suggest that SIRT6-β-catenin signaling might be a new therapeutic target of ovarian carcinomas.